CX3CL1 Recruits NK Cells Into the Central Nervous System and Aggravates Brain Injury of Mice Caused by Angiostrongylus cantonensis Infection - Zhang, Rong; Miao, Tingting; Qin, Min; Zhao, Chengsi; Wang, Wei; Zhang, Chengcheng; Liu, Xinjian; Chen, Ying; Chen, Ailing; Wang, Yong (Frontiers in Cellular and Infection Microbiology, 2021)
Background Angiostrongylus cantonensis (A. cantonensis), is a food-borne zoonotic parasite that can cause central nervous system (CNS) injury characterized by eosinophilic meningitis. However, the pathogenesis of angiostrongylosis remains elusive. Natural killer cells (NK cells) are unique innate lymphocytes important in early defense against pathogens. The aim of this study was to investigate the role of NK cells in A. cantonensis infection and to elucidate the key factors that recruit NK cells into the CNS. Methods Mouse model of A. cantonensis infection was established by intragastric administration of third-stage larvae. The expression of cytokines and chemokines at gene and protein levels was analyzed by qRT-PCR and ELISA. Distribution of NK cells was observed by immunohistochemistry and flow cytometry. NK cell-mediated cytotoxicity against YAC-1 cells was detected by LDH release assay. The ability of NK cells to secrete cytokines was determined by intracellular flow cytometry and ELISA. Depletion and adoptive transfer of NK cells in vivo was induced by tail vein injection of anti-asialo GM1 rabbit serum and purified splenic NK cells, respectively. CX3CL1 neutralization experiment was performed by intraperitoneal injection of anti-CX3CL1 rat IgG. Results The infiltration of NK cells in the CNS of A. cantonensis-infected mice was observed from 14 dpi and reached the peak on 18 and 22 dpi. Compared with uninfected splenic NK cells, the CNS-infiltrated NK cells of infected mice showed enhanced cytotoxicity and increased IFN-γ and TNF-α production ability. Depletion of NK cells alleviated brain injury, whereas adoptive transfer of NK cells exacerbated brain damage in A. cantonensis-infected mice. The expression of CX3CL1 in the brain tissue and its receptor CX3CR1 on the CNS-infiltrated NK cells were both elevated after A. cantonensis infection. CX3CL1 neutralization reduced the percentage and absolute number of the CNS-infiltrated NK cells and relieved brain damage caused by A. cantonensis infection. Conclusions Our results demonstrate that the up-regulated CX3CL1 in the brain tissue recruits NK cells into the CNS and aggravates brain damage caused by A. cantonensis infection. The findings improve the understanding of the pathogenesis of angiostrongyliasis and expand the therapeutic intervention in CNS disease.